Comportamento alimentar do Matrinxã - Brycon cephalus (Gunther, 1869) em tanques de cultivo - Scorvo, Célia Maria Dória Frasca [UNESP] (Universidade Estadual Paulista (Unesp), 1999)
The work aimed the study of the feeding behavior of the matrinxã, Brycon cephalus, in rearing ponds. Analyzed parameters were the period and schedule of feeding, satiation time, speed and index of ingestion and feeding frequency in different periods of the day. The work was carried out on the Aquaculture Center of UNESP - CAUNESP, Jaboticabal, SP, located at 21º15'22 S and 48º858 W. The observations were accomplished in four stages, corresponding to different experimental researches, from May, 1997 to January, 1998, in 16 tanks of 50m2. In the first-stage (Research I), fish of 13.17g were fed to the satiation, in different periods of the day morning, noon, afternoon, morning + noon, morning + afternoon e noon + afternoon with extruded commercial pellets, of 35% of crude protein. The food consumption was greater in the fishes fed twice a day, at noon and in the afternoon. In the second stage (Research II), it was analyzed the feed consumption, ingestion index, satiation time and velocity of ingestion. Fishes of 232.13g ± 0,95 were fed extruded commercial pellets of 32% of crude protein in three periods of ther day: morning, noon and afternoon. No significant statistical difference Observed in the analyzed parameters, although a greater food consumption was noted, in the afternoon (2,47g(m); 2,86g(n) and 3,88g(a) and larger ingestion index (1,08%, 1,26% and 1,69% respectively). The same fishes previous mean weight of 233.98 ± were used Research III and the feed consumption was observed in periods of two hours from 7 AM to 7 PM. The variance analysis and the Tukey test demonstrated that the greater consumption happened when the matrinxã was fed at 5 PM, whereas no significant difference took place between 3 and 7 PM, evidencing that the feeding can be efficient in this whole afternoon period. The Research IV, during of 57 days, tested feeding once in the morning; once in the afternoon; twice ...

O objetivo deste trabalho foi estudar o comportamento alimentar do matrinxã, Brycon cephalus, em tanques de cultivo, analisando o período e horário de alimentação, tempo de saciação, velocidade de ingestão, índice de ingestão alimentar e freqüência de alimentação em diferentes horários do dia. O trabalho foi realizado no Centro de Aquicultura da UNESP- CAUNESP, Jaboticabal, SP, localizado à 21º5'22 Lat. S e 48º8'58 Long. W. No período de maio de 1997 a janeiro de 1998, foram realizados quatro ensaios, utilizando-se 16 tanques de 50m2. No ensaio I, peixes com peso médio de 13,7g foram alimentados até a saciação, com ração comercial extrusada, contendo 35% de proteína bruta, em diferentes períodos do dia: manhã (m), meio do dia (md), tarde (t); manhã mais meio do dia (m+md); manhã mais tarde (m+t) e meio do dia mais tarde (md+t). O consumo de ração foi destacadamente maior nos peixes arraçoados duas vezes ao dia, no período do (md) e à (t). No ensaio II, foram analisados os consumos de ração, índice de ingestão, tempo de saciação e velocidade de ingestão em 3 períodos do dia: manhã, meio do dia e tarde. Os peixes que estavam com peso médio de 232,13g (± 0,95), foram alimentados com ração comercial extrusada, com 32% de proteína bruta. Não foram observadas diferenças estatísticas significativas nos parâmetros analisados, embora tenha sido observado para o período da tarde um consumo médio relativamente maior (2,47g (m); 2,86g (md) e 3,88g (t)) e maiores médias dos índices de ingestão (1,08%, 1,26% e 1,69% respectivamente). No ensaio III, foram utilizados os mesmos peixes do ensaio II, com peso médio de 233,98g (±5,60) avaliando-se o consumo médio de ração de duas em duas horas, das 7 às 19 horas. A análise de variância e o teste de Tukey demonstraram que o maior consumo ocorreu quando o matrinxã foi alimentado às 17 horas...
Keywords: Peixe; Peixe - Nutrição; Brycon; Habitos alimentares; Tanques; Fishes